1999
DOI: 10.1152/ajpendo.1999.276.5.e930
|View full text |Cite
|
Sign up to set email alerts
|

Rapid reversal of the effects of the portal signal under hyperinsulinemic conditions in the conscious dog

Abstract: Experiments were performed on two groups of 42-h-fasted conscious dogs ( n = 6/group). Somatostatin was given peripherally with insulin (4-fold basal) and glucagon (basal) intraportally. In the first experimental period, glucose was infused peripherally to double the hepatic glucose load (HGL) in both groups. In the second experimental period, glucose (21.8 μmol ⋅ kg−1 ⋅ min−1) was infused intraportally and the peripheral glucose infusion rate (PeGIR) was reduced to maintain the precreating HGL in the portal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…In response to a hyperglycemic, hyperinsulinemic challenge, the liver reacts by switching from net glucose output to net uptake. Previous studies have demonstrated that activation of the portal signal by portally administered glucose in combination with hyperinsulinemia results in hepatic glucose uptake of 4 -5 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 (8). Thus, the hepatic response in the IVC group was predictable, with nearly 5 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 of glucose taken up at 30 min.…”
mentioning
confidence: 89%
“…In response to a hyperglycemic, hyperinsulinemic challenge, the liver reacts by switching from net glucose output to net uptake. Previous studies have demonstrated that activation of the portal signal by portally administered glucose in combination with hyperinsulinemia results in hepatic glucose uptake of 4 -5 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 (8). Thus, the hepatic response in the IVC group was predictable, with nearly 5 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 of glucose taken up at 30 min.…”
mentioning
confidence: 89%
“…A potential benefit of the enteral route is that when only glucose is delivered via the enteral route in the acute setting it enhances net hepatic glucose uptake (NHGU) to a greater extent than when glucose is delivered via a peripheral route; this route-dependent effect has been termed the "portal signal" (7,20). The portal signal can rapidly (Ͻ15 min) augment NHGU; it does not require the presence of hyperglycemia or hyperinsulinemia (11). Surprisingly, when TEN is administered chronically in unstressed animals, which should activate the portal signal, NHGU is not any greater than that seen with TPN alone (1).…”
mentioning
confidence: 99%
“…However, it has vasoactive effects in skeletal muscle in vivo, causing the channeling of blood away from the vessels supplying oxygen and nutrients to skeletal muscle ("nutritive flow") and into other vessels (those supplying connective tissue and associated adipocytes, creating "nonnutritive flow") and reducing muscle and hindlimb nutrient uptake (8,30). Finally, it is worth noting that our laboratory (1,17,18) has previously observed a reciprocal relationship between hepatic and peripheral glucose uptake, such that when NHGU is stimulated by the presence of the "portal signal," there is a concomitant decrease in non-HGU. Thus the presence of an integrated mechanism for partitioning glucose disposal among the tissues in the postprandial state may explain the tendency toward suppression of non-HGU concomitant with stimulation of NHGU in the FLUV group.…”
Section: Discussionmentioning
confidence: 98%
“…During the 1st h of glucose infusion, the non-HGU was corrected for the glucose required to fill the pool, using a pool fraction of 0.65 (9) and assuming that the volume of distribution for glucose equaled the volume of the extracellular fluid or ϳ22% of the dog's weight (32). For all glucose balance calculations, glucose concentrations were converted from plasma to blood values by using correction factors (ratio of the blood to the plasma concentration), as previously established in our laboratory (17,18,27).…”
Section: Methodsmentioning
confidence: 99%